Требуются девушки для работы в Японии: [роман] / Юлия Шилова - Шилова Юлия Витальевна (Час криминала, 2000)
Экземпляры: ф.18 (2001) / Инвентарный номер: 43135 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44